Peningkatan Keterampilan Menulis Narasi Menggunakan Model Examples Non Examples pada Siswa Kelas IV SD - Husnah, Mirdhatul; Mahjuddin, Ritawati; Mansurdin, Mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of the study was to describe the improvement of narrative writing skills using Examples Non Examples models in fourth grade students of SD Negeri 04 Pisang, Padang city. The research subjects were as many as 26 teachers as observers, researchers, and fourth grade students consisting of 11 women and 15 men. The results of the pre-writing phase of the cycle I obtained an average score of 51.4% increased to 88.9% in the second cycle. The results of the research in the writing phase of cycle I obtained an average value of 49.4% increased to 80.57% in cycle II. The results of the research in the first cycle in the post-writing phase of cycle I obtained an average value of 54.4% increased to 87.18% in cycle II. It can be concluded that Examples Non Examples models can improve students' narrative writing skills in elementary school. Keywords: narrative writing,Examples Non Examples.